2015
DOI: 10.4028/www.scientific.net/amr.1109.35
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles Using Momordica Charantia Fruit Extracts

Abstract: The synthesis of nanoparticles is in the spotlight in modern nanotechnology. In recent years, the development of competent green chemistry methods for synthesis of metal nanoparticles (NPs) has become a main limelight of researchers. Biological synthesis of nanoparticles using plant extract is currently under exploitation. The first time in this paper we have reported the green synthesis of silver nanoparticles (AgNPs) by reduction of silver nitrate, using fruit extracts of Momordica charantia (bitter melon); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Based on the UV-vis results, an increased in the amount of GM peels powder and concentration of AgNO 3 increased the peak intensity of UV-vis spectra. This result suggests that higher amount of GM peels powder and concentration of AgNO 3 speed up the formation of AgNPs as more AgNPs were formed which is consistent with the previous result [48]. Red shift was observed due to the increase of interactions between GM peels extract and available silver ions, hence resulting in the increase of AgNPs size [49].…”
Section: Discussionsupporting
confidence: 89%
“…Based on the UV-vis results, an increased in the amount of GM peels powder and concentration of AgNO 3 increased the peak intensity of UV-vis spectra. This result suggests that higher amount of GM peels powder and concentration of AgNO 3 speed up the formation of AgNPs as more AgNPs were formed which is consistent with the previous result [48]. Red shift was observed due to the increase of interactions between GM peels extract and available silver ions, hence resulting in the increase of AgNPs size [49].…”
Section: Discussionsupporting
confidence: 89%
“…69 Another work also found that as the Ag + concentration increased from 324 to 585 mg L −1 , more nuclei with smaller sizes were found, while increasing the Ag + from 585 to 755 mg L −1 caused the growth of crystals around the nucleus with an increase in average particle size. 70 It has been suggested that an increase in Ag + concentration to some extent leads to an increase in the reaction rate, 71 which caused most Ag + to be consumed in the formation of nuclei and thus stopped the secondary reduction process on the surface of the preformed nuclei, resulting in the formation of smaller size particles. 72 AgNP Formation Mechanism by S. oneidensis MR-1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…reducing watery silver nitrate (Varghese et al, 2015). Momordica charantia leaf extract used as a green source for both reductant and stabilizing in biosynthesis of Ag NPs (Nahar et al, 2015).…”
Section: Biosynthesis Silver Nanoparticles By Plant Extractsmentioning
confidence: 99%